Analysis of Momentum and Impulse Misconceptions of College Students Using Four-Tier Diagnostic Tests - Amira Setiani; Firmansyah, Danny; Ramadhani, Cahyani Intan (Yayasan Nurul Yakin Bunga Tanjung, 2023)
This research aims to discover misconceptions about momentum and impulse concepts. The research method used in this research is a mixed method. The subjects of this research were students majoring in physics from the classes of 2019, 2020, and 2021 who had taken the basic physics course I, with a total sample of 44 students. The instrument used was 15 four-level multiple diagnostic tests. Research data was obtained based on student answer patterns on a four-level multiple-choice test. The results of the research show that students' conceptual understanding of momentum and impulse material using the four-level diagnostic test is still relatively low, as seen from the percentage of students who partially understand the concept at 46%, understand the concept at 30%, negative misconceptions at 10%, positive misconceptions at 9%, and positive misconceptions at 5%. Some of the misconceptions experienced by students regarding the concepts of momentum and impulse include: first, students assume that only mass influences the amount of momentum; second, they assume that the total momentum of a system of isolated objects is not constant; third, assume that the total momentum of a system of isolated objects is not constant, the fourth assumes that two objects of the same mass have different speeds, the sixth assumes that changes in the speed of a particle are only influenced by force and time and the last, namely the seventh, assumes that the process of collisions on smooth surfaces will move all objects.